Anatomy and mechanical properties of the anal sphincter muscles in healthy senior volunteers. Issue 8 (15th March 2018) - Brusa, T.; Abler, D.; Tutuian, R.; Gingert, C.; Heverhagen, J. T.; Adamina, M.; Brügger, L. E.; Büchler, P.
Abstract: Background: A large proportion of age‐related fecal incontinence is attributed to weakness or degeneration of the muscles composing the anal continence organ. However, the individual role of these muscles and their functional interplay remain poorly understood. Methods: This study employs a novel technique based on the combination of MR imaging and FLIP measurements (MR‐FLIP) to obtain anatomical and mechanical information simultaneously. Unlike previous methods used to assess the mechanics of the continence organ, MR‐FLIP allows inter‐individual comparisons and statistical analysis of the sphincter morpho‐mechanical parameters. The anatomy as well as voluntary and involuntary mechanical properties of the anal continence organ were characterized in 20 healthy senior volunteers. Results: Results showed that the external anal sphincter (EAS) forms a funnel‐like shape with wall thickness increasing by a factor of 2.5 from distal (6 ± 0 mm) to proximal (15 ± 3 mm). Both voluntary and involuntary mechanical properties in this region correlate strongly with the thickness of the muscle. The positions of least compliance and maximal orifice closing were both located toward the proximal EAS end. In addition, maximal contraction during squeeze maneuvers was reached after 2 s, but high muscle fatigue was measured during a 7 s holding phase, corresponding to about 60% loss of the energy produced by the muscles during the contraction phase. Conclusions: This work reports baseline parameters describing the morpho‐mechanical condition of the sphincter muscle of healthy elderly volunteers. New parameters were also proposed to quantify the active properties of the muscles based on the mechanical energy associated with muscle contraction and fatigue. This information could be used to assess patients suffering from AI or for the design of novel implants. Abstract : The mechanisms by which continence is maintained remain poorly understood. Therefore, we report a first statistical analysis of the involuntary (compliance) and voluntary (muscle work) mechanical properties of the healthy continence organ along the anal canal. This work presents baseline parameters for implant design and proposes new mechanical biomarkers for quantifying continence. In addition, this study provides evidence that the proximal segment of the anal canal plays a prominent role in mechanically maintaining continence.